Headache and Physical and Sexual Abuse Among Jewish and Arab Adolescents in Israel. (April 2014) - Genizi, Jacob; Srugo, Isaac; Kerem, Nogah C.
The purpose of the present study was to evaluate the relationship between headaches and physical and sexual abuse. A self-administered, anonymous questionnaire was presented to 2088 tenth grade students in Northern Israel. Participants were Jews and Arabs between the ages of 15 to 16 years. Arab adolescents comprised 55% of the analyzed sample and adolescent Jews 45%. With regard to gender, 56% of participants were females. Of the Arab participants, 18.6% reported having frequent headaches, less than that reported in the Jewish group (27.9%). Jewish girls who were physically abused during childhood had a higher prevalence of frequent headaches (55% vs 33% P < .001). Jewish students who reported being sexually abused had higher headache prevalence as well (44.4% vs 27.3% P = .05). In conclusion, adolescents who reported to have been physically or sexually abused report a higher prevalence of headache compared to their peers.